Identifying and addressing barriers and opportunities for bovine respiratory disease complex vaccination: a consensus paper on practical recommendations for best practise vaccination - Yarnall, Matt; Amovilli, Federica; Assié, Sébastien; Bokma, Jade; Pugh, Matt; Werling, Dirk (Frontiers in Veterinary Science, 2024)
Many questions are raised, and challenges faced in the new era of (intranasal) bovine respiratory disease complex vaccination. An increase in vaccination rate is expected, due to its positive impact on cattle health, reduction of antimicrobial use, and economic factors. However, engagement of farmers and veterinarians with regards to vaccination is often affected by limitation, resulting in the development of barriers to vaccination, but also opportunities to overcome these. The objective of the report is to provide practical recommendations and a consensus on best practices for BRDC vaccination, addressing barriers faced by veterinarians and farmers. The report combines an evidence review with expert opinions and includes discussions on different vaccination approaches, such as intranasal and systemic protocols. As result of the discussions, several barriers to BRDC vaccination were identified, including a lack of knowledge or visibility of the disease's impact, the preference for blanket antibiotic use over vaccination, resistance to change, the need for visible success, uncertainty about the best time to vaccinate, and concerns about adverse reactions and vaccine efficacy in the presence of maternal antibodies. While these barriers seem substantial, they provide opportunities for the veterinary sector, Indeed, veterinarians are encouraged to use the argumentation presented, along with local case studies and diagnostic testing to highlight the impact of disease, whilst conducting calf health audits, ensuring expectations are managed to achieve visible success. Overall, this consensus paper aims to provide practical recommendations and support for veterinarians and farmers to overcome barriers and increase BRDC vaccination rates in cattle.